Rewriting the Writing Mother in Marie Darrieussecq's Le Bébé - Claire Marrone (Studies in 20th & 21st Century Literature, 2008)
This article studies the innovative maternal portrait in Marie Darrieussecq's Le Bébé (2002), the autobiographical story of a mother's first nine months with her newborn son. It also examines how Darrieussecq engages in the riveting debate surrounding maternal creativity. On the one hand, Le Bébé is a "success story," one that attests to the victories of the feminist movement. On the other hand, the text examines the new challenges of today's writing mothers. Throughout the work, the "mother as scientist" analyzes her developing child while the nurturing "mom" pens her joys, discoveries, and difficulties. The article concludes that because the researcher is also the mother, and because this marriage of roles in relation to one’s own child is somewhat jarring, Darrieussecq achieves a striking and truly contemporary maternal portrait.
Keywords: maternal portrait; Marie Darrieussecq; Le Bébé; autobiography; motherhood; baby; mother; child